1992
DOI: 10.1002/cjce.5450700419
|View full text |Cite
|
Sign up to set email alerts
|

Spectral measurement of the complex refractive index of fly ashes of canadian lignite and sub‐bituminous coals

Abstract: The complex spectral refractive index (absorption index) of fly ash from two generating stations burning Canadian lignite and sub‐bituminous coals have been examined by two different techniques. Ash samples collected at different combustion conditions were analyzed. It is shown that the absorption index of both ashes is in the range of 0.004 to 0.018 in the wavelength range of 0.7‐2.5 μm. The effects of presence of carbonaceous material in ashes, iron content and different operating (combustion) conditions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In order to properly simulate the scattering processes, accurate information on particle refractive index are required, beyond those on particle size distribution already provided above. Accurate measurements of lignite refractive index were reported by Lohi et al (1992), who observed values of the real and imaginary part of the complex refractive index of 1.70 and 1 × 10 −6 , respectively. Similar values were reported by McCartney and Ergun (1962) and Read (2008).…”
Section: Hygroscopic and Scattering Behaviour Of Lignite Particlesmentioning
confidence: 59%
“…In order to properly simulate the scattering processes, accurate information on particle refractive index are required, beyond those on particle size distribution already provided above. Accurate measurements of lignite refractive index were reported by Lohi et al (1992), who observed values of the real and imaginary part of the complex refractive index of 1.70 and 1 × 10 −6 , respectively. Similar values were reported by McCartney and Ergun (1962) and Read (2008).…”
Section: Hygroscopic and Scattering Behaviour Of Lignite Particlesmentioning
confidence: 59%
“…Accurate measurements of lignite refractive index were reported by Lohi et al (1992), who observed values of the real and the size growth experienced by these particles during their adiabatic ascent. Thus, we believe that the observed dark band phenomenon is associated with the oscillations in particle backscattering efficiency, ultimately leading to Mie back-scattered signal intensity fluctuations.…”
mentioning
confidence: 57%
“…In order to properly simulate these scattering processes, accurate information on particle refractive index are required, besides those on particle size distribution already provided above. Accurate measurements of lignite refractive index have been reported by Lohi et al (1992) [6], who observed values of the real and imaginary part of the complex refractive index of 1.70 and 1x10 -6 , respectively. Simulations of the scattering properties of lignite particles are illustrated in figure 4.…”
Section: Hygroscopic and Scattering Behavior Of Lignite Particlesmentioning
confidence: 72%